Population mobility and the links between migrants and the family back home in Ngawis Village, Gunung Kidul Regency, Yogyakarta Special Region - Ida Bagus Mantra (Indonesian Journal of Geography, 1988)
The total population of Yogyakarta Special Region was 2,966,549 persons in 1985, while the population density was 931 persons/sq.km. The Yogyakarta Special Region is one of the poor areas of Java in an economic sense.The annual rate of its population growth is much lower than those of other provinces in Java. The region experienced a net loss of population through migration. The losses were greater in the poor areas of Gunung Kidul, one of its regencies.This study aims at developing the knowledge on the nature and incidence of population mobility from the rural to the urban areas, and investigating the extent and nature of the links established and maintained between the area of origin and the area of destination, by temporarily returning migrants in Ngawis Village of Gunung Kidul.The main reason for migrating out of the village is an economic one. Although the greater part of returning migrants stated that their economic conditions improved after moving out, the income they receive monthly is still low. The link between migrants and their relatives back home is very intensive. They maintain contact by visiting, sending letters, money and goods, and exchange views and ideas on developmental issues.